STRUKTUR KEMEPILIKAN, RISIKO DAN KEBIJAKAN KEUANGAN: ANALISIS PERSAMAAN SIMULTAN - Fitri Ismiyanti, Mamduh M.Hanafi (UGM, 2004)
The research explores using simultaneous regression to examine the interdependance relationship between managerial ownershiip, risk, dividend policy, institutional ownership, and levarege policy for Indonesian capital market. The research tries to explain how the relationships in financial policy for manufacture firms in Indonesia. We use five models of regression to represent five different policies in firms that reflect the agency issues and conflct of interset between agent (manager), and procopal (insider and outsider shareholders). Jensen and meckling (1976) argued that agency problem arise from separation of ownership and control. Each of five policies in this research is represent conflict of interst between agend and principal. The research combined models from Crutchley, Jensen, Jahera and Raymond (1999), and Chen and Steiner (1999) to construct five-regression policies model.